Intercalation‐Activated Layered MoO3 Nanobelts as Biodegradable Nanozymes for Tumor‐Specific Photo‐Enhanced Catalytic Therapy - Zhou, Zhan; Wang, Yanlong; Peng, Feng; Meng, Fanqi; Zha, Jiajia; Ma, Lu; Du, Yonghua; Peng, Na; Ma, Lufang; Zhang, Qinghua; Gu, Lin; Yin, Wenyan; et al. (Angewandte Chemie (International ed.), 2022)
The existence of natural van der Waals gaps in layered materials allows them to be easily intercalated with varying guest species, offering an appealing strategy to optimize their physicochemical properties and application performance. Herein, we report the activation of layered MoO3 nanobelts via aqueous intercalation as an efficient biodegradable nanozyme for tumor‐specific photo‐enhanced catalytic therapy. The long MoO3 nanobelts are grinded and then intercalated with Na+ and H2O to obtain the short Na+/H2O co‐intercalated MoO3−x (NH−MoO3−x) nanobelts. In contrast to the inert MoO3 nanobelts, the NH−MoO3−x nanobelts exhibit excellent enzyme‐mimicking catalytic activity for generation of reactive oxygen species, which can be further enhanced by the photothermal effect under a 1064 nm laser irradiation. Thus, after bovine serum albumin modification, the NH−MoO3−x nanobelts can efficiently kill cancer cells in vitro and eliminate tumors in vivo facilitating with 1064 nm laser irradiation. Aqueous intercalation is proposed here as a promising strategy to activate the enzyme‐mimicking catalytic activity of layered MoO3 nanobelts for the generation of reactive oxygen species including ⋅OH and ⋅O2− in a tumor microenvironment, making it an efficient biodegradable nanozyme for tumor‐specific photo‐enhanced catalytic therapy.